Trade Facilitation Measures in South Asian FTAs: An Overview of Initiatives and Policy Approaches - Sachin Chaturvedi (Asia-Pacific Research and Training Network on Trade (ARTNeT), 2007)
In this paper authors have made an effort to take a stock of various FTAs in South Asia from the point of view of incorporation of TF measures in the text of FTAs. Authors also look into the individual initiatives being made by the South Asian countries for advancement of trade facilitation especially in context of Articles V, VIII and X.
Keywords: F1; 330; FTA; South Asia; Articles V; VIII; and X; Trade Facilitation